Characterizations of Generalized Paracompactness in Ideal Topological Spaces (European Journal of Pure and Applied Mathematics, 2025)
The concept of $δ\text{-}{β}_{\mathcal{I}}$-paracompactness in ideal topological spaces is introduced as a weaker form of $β$-paracompactness, which was looked at in \cite{YO}. This study examines several characterizations of $δ\text{-}{β}_{\mathcal{I}}$-paracompact spaces and its subsets. Furthermore, we investigate the invariants of $δ\text{-}{β}_{\mathcal{I}}$-paracompactness through functions.
Keywords: locally finite collection; ideal topological space; $δ\text{-}{β}_{\mathcal{I}}$-paracompactness